ANALISIS FILM PUTIH ABU-ABU DAN SEPATU KETS MELALUI LAYANAN BIMBINGAN DAN KONSELING UNTUK MENCEGAH PERGAULAN BEBAS DI SMA KARYA 45 BANGUN REJO MUSI RAWAS - Prihatin, Ike Agus (Jurnal Empati Bimbingan dan Konseling, 2022)
This research is motivated by students stating that they are lazy to follow lessons such as not taking attendance, not doing assignments, spending time playing games, and holding meetings with the opposite sex in one basecamp to have fun with their girlfriends. From these actions, which caused students to drop out of school due to pregnancy outside of marriage. The aim of this research is to find out whether the effect of the film White Gray and Sneakers is effective through guidance and counseling services to prevent promiscuity, this study uses a quantitative descriptive method. Based on the results of the study, it was found that the level of students' understanding of promiscuity before the screening of the film White Gray and Sneakers had an average value of 84.04, the level of understanding of students about promiscuity after the screening of the film White Gray and Sneakers had an average value of 86, 98 with a difference of 2.94. The results of statistical tests using the Paired Sample T-test showed that the P value 0.05, which was 0.000, meaning that there was an effect of the effect of the White Gray film and effective sneakers through guidance and counseling services to prevent promiscuity in SMA Karya 45 Bangunrejo Musi Rawas .